2018
DOI: 10.1080/09669760.2018.1479632
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ experience with ‘near and clear’ educator talk: individual variation and its relationship to indicators of quality

Abstract: This study investigated the quantity of audible and intelligible ('near and clear') educator talk directly experienced by under-two-year-old infants attending early childhood education and care (ECEC) programs and examined whether the quantity of educator talk was related to characteristics of quality in their ECEC room. Participants were 57 infants attending separate infant rooms in and around the Sydney metropolitan area, Australia. Each infant was observed for 3 hours, wearing a small, customdesigned digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Firstly, our findings add to a growing body of work that draws attention to the different quantities and qualities of facilitative talk in ECEC settings (e.g., Degotardi et al, 2018;Dickenson et a., 2014;Hu et al, 2017;National Institute of Child Health and Human Development Early Child Care Research, 2000;Vernon-Feagans & Bratsch-Hines, 2013) Within this context, when educators recognise the educational affordances of reasoning talk, they can increase children's learning opportunities through more frequent use of this type of talk.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Firstly, our findings add to a growing body of work that draws attention to the different quantities and qualities of facilitative talk in ECEC settings (e.g., Degotardi et al, 2018;Dickenson et a., 2014;Hu et al, 2017;National Institute of Child Health and Human Development Early Child Care Research, 2000;Vernon-Feagans & Bratsch-Hines, 2013) Within this context, when educators recognise the educational affordances of reasoning talk, they can increase children's learning opportunities through more frequent use of this type of talk.…”
Section: Discussionmentioning
confidence: 63%
“…Secondly, many studies have demonstrated that the level of educator qualification is significantly related to the quality of their interactions with very young children (Degotardi, Han, & Torr, 2018;Degotardi, Torr, & Nguyen, 2016;Manlove, Vazquez, & Vernon-Feagans, 2008; National Institute of Child Health and Human Development Early Child Care…”
Section: The Present Studymentioning
confidence: 99%
“…In this vein, for example, emphasis has been placed on the impact of educators' language on child language acquisition (Muhinyi & Rowe, 2019), on the specific development of expressive language through play with infants (Cuellar & Farkas, 2018), and/or on specific cognitive skills such as print concept, letter naming and/or phonological awareness (Piasta et al, 2019). In addition, recent studies have examined more specific properties of language and the impact of educator syntax on infants' learning of new vocabulary (Farrow et al, 2020), vocabulary size, syntactical complexity and lexical diversity both of educators and infants (Pizarro et al, 2019), near and clear or far and unclear educator talk (Degotardi et al, 2018), and/or preferences for storytelling and reading versus writing activities and their differential association with verbal syntactic complexity and the acquisition of new vocabulary (Torr, 2020).…”
Section: Evidence-based Characterizations Of Early Childhood Educatorsmentioning
confidence: 99%
“…Recent work, however, has shown that infants' ECEC language experiences exhibit broad variation in terms of both quantity and quality (Degotardi, Han, and Torr 2018a;Torr and Pham 2016), raising concerns that infant ECEC programs may provide limited opportunities for early language development (Norris 2014; Thomason and La Paro 2009). Efforts are therefore needed to examine factors which may explain this variation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, because early childhood professional training is designed to build educators' knowledge base, we investigate associations between these educators' knowledge and reported approaches and their level of early childhood qualification. While the qualification level of infant educators has been found to explain the quality of their interactions with infants (Burchinal, Cryer, Clifford, and Howes 2002;Degotardi et al 2018a;Manlove, Vaquez and Vernon-Feagans 2008),…”
Section: Introductionmentioning
confidence: 99%